Airport connectivity evaluation: The study of Thailand - Apichat Sopadang (2018)
© IEOM Society International. Air connectivity is key to opening a country's economic growth potential because it allows the country to tempt business investment and human capital. Meanwhile, the continued growth of Low-Cost Carriers (LCCs) has increased penetration into emerging markets. Thereby, these have made air travel more accessible. This paper aimed to evaluate airport connectivity of Don Mueang International Airport, Thailand which now can call the busiest LCCs international airport in the world (Based on 2015). Then, used that result compared to the other LCCs international airport in South-East Asia. The destination is the international airport in the country of ASEAN plus 3 Region. The NETSCAN Connectivity Index was used to evaluate the connectivity units in this paper. The result of shown the capability of Don Mueang International Airport to become one of the LCCs regional hubs for ASEAN plus 3 Region.